Lossless compression for digital fundus images - Liu, Xinhua. (2008)
Medical images in digital format are usually very large. As more and more medical imaging switched to digital format, transmission and storage of these images becomes a problem because of their large sizes. In this thesis, we developed a lossless compression algorithm and calibrated it specifically to optimize the compression performance for color fundus images.